2011
DOI: 10.1021/ol203016c
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of HNO Production from N,O-bis-Acylated Hydroxylamine Derivatives

Abstract: A wide range of N,O-bis-acylated hydroxylamine derivatives with chloro or arenesulfonyl leaving groups, and a related set of N-hydroxy-N-acylsulfonamides, have been synthesized and evaluated for nitroxyl (HNO) production. Mechanistic studies have revealed that the observed aqueous chemistry is more complicated than originally anticipated, and have been used to develop a new series of efficient HNO precursors (4u-4x, 7c-7d) with tunable half-lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…29 Based on this initial work, we reported modified N,O-bis-acylated hydroxylamine derivatives with arenesulfonyl leaving groups that produce nitrosocarbonyls nonenzymatically under physiological conditions. 17 Mechanistic studies revealed that the chemistry of these donors is complicated and that non-HNO producing pathways (acyl migration and amide hydrolysis) can be dominant.…”
Section: ■ Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…29 Based on this initial work, we reported modified N,O-bis-acylated hydroxylamine derivatives with arenesulfonyl leaving groups that produce nitrosocarbonyls nonenzymatically under physiological conditions. 17 Mechanistic studies revealed that the chemistry of these donors is complicated and that non-HNO producing pathways (acyl migration and amide hydrolysis) can be dominant.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Accessing other HNO donors with different release rates under physiological conditions is important to assess the impact that HNO may potentially have on the treatment of diseases. Piloty’s acid (PA) derivatives, acyloxy nitroso (AcON) compounds, (hydroxylamino)­pyrazolone (HAPY), , and (hydroxylamino)­barbituric acid (HABA) derivatives (Figure ) are among a limited number of physiologically compatible HNO donors with tunable half-lives that have been reported. Continued efforts are required to develop other potential HNO donors that can be used under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…81 A library of N , O -bis-acylated N- hydroxysulfonamide derivatives with tunable half-lives (minutes - hours) demonstrate efficient HNO release at physiological pH (Figure 10). 82 Knaus prepared ethanesulfohydroxamic acid esters of indomethacin, ( S )-naproxen, and ibuprofen as potential clinical prodrugs (Figure 10). 83 These compounds display diverse biological activities and show much higher NO release compared to other N -hydroxysulfonamides.…”
Section: Advances In Hno Sourcesmentioning
confidence: 99%
“…Piloty's acid (PA) derivatives and acyloxy nitroso compounds (AcON) represent other types of HNO donors that have been developed with tunable half-lives. [12][13][14][15][16][17] Our group has recently reported two new series of HNO donors with half-lives that can be varied from minutes to hours under physiological conditions: (hydroxylamino)pyrazolone (HAPY) and (hydroxylamino)barbituric acid (HABA) derivatives. [18][19][20] In addition to these examples, the continued development of efficient HNO donors is important to expand the research tools available to understand the potential role of HNO in biological processes.…”
Section: Introductionmentioning
confidence: 99%